Spotting Rooms for the Dignity of Jomblo in Higher Education - Melliani, Mika; Munthe, Yesyurun; Simanjuntak, Nova Lady (Eduscape : Journal of Education Insight, 2023)
This research aims to see the extent of perception, stigma and behavior of someone who holds the status of single. The research subjects consisted of students and those who have worked in a company. The stigma of being single can lead a person to be traumatized, less confident, aloof and powerless over themselves and outside themselves. Nonetheless, the four research subjects described being single as activity, creation, self-development, strengthening of the main self and carrying oneself through a good response to something that appears outside oneself. This study is a qualitative research by considering the case of singles, happiness, and unrest through literature review. The literature review comes from journals of recent findings as a secondary source in a study. The statement of this research is that being single is not only a choice, but the ability to build self and dignity in a process and inherent. The results showed that the four research subjects were able to resist stigma with constructive work in the classroom or at work as a stabilization of self-recognition to exist on the onslaught of stigma.